Loewe Store at Serrano Street, Architect Javier Carvajal: Architectural Project analysis - Josa Martínez, María Eugenia; Villanueva Fernández, María (Estoa. Journal of the Faculty of Architecture and Urbanism, 2017)
Between 1959 and 1964, Javier Carvajal architectural team built thirteen boutiques for Spanish fashion firm Loewe. The innovative design of the boutiques was part of a period of renewal and makeover of the brand, boosted by the cultural modernization that was taking place in Spain. It was at this point when collaborations between architects, artists and fashion entrepreneurs such as Carvajal and Loewe started to increase, as a way to transform entirely the boutiques, products, commercial strategies and corporate image of the brand as a whole. A critical analysis of the boutiques is crucial to get to know the strategies Javier Carvajal used in his designs for Loewe. It is known, for example, that Carvajal transformed Loewe’s boutique located in Serrano Street (Madrid) into an exhibition hall in order to present the new products of the firm as true fashion masterpieces. This and other examples are showcased in this article, which aims to produce a methodological way to analyse the architecture of shops based in Carvajal and Loewe’s work. Keywords: architectural analysis, design, Javier Carvajal, Loewe, Retail Stores.